Pola Komunikasi Interpersonal Polisi dan Masyarakat dalam Kegiatan Patroli Kepolisian di Kecamatan Keban Agung, Kabupaten Lahat - Gilang Putra Ramadhan; Desy Misnawati (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the patterns of interpersonal communication between police officers and the community in police patrol activities in Keban Agung District, Lahat Regency. Interpersonal communication is an important element in building closeness, trust, and cooperation between the police and the community in maintaining public security and order. This study employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving police officers and community members who were directly engaged in or interacted with patrol activities. The findings show that the interpersonal communication patterns established during police patrols were direct, dialogic, persuasive, and situational. Police officers not only delivered messages related to security and public order, but also developed closer relationships with the community through a humanistic approach, the use of easily understood language, and interactions adjusted to the social characteristics of the local community. Such communication contributed to increasing the community’s sense of security, strengthening public trust in the police, and encouraging community participation in maintaining environmental safety. However, this study also found several communication barriers, including differences in perception, limited interaction time, and uneven levels of community participation. Therefore, it is necessary to strengthen interpersonal communication strategies in a more consistent, participatory, and sustainable manner so that police patrol activities function not only as a form of security monitoring, but also as a means of building social partnership between the police and the community.